Implementasi Peer Education dalam Meningkatkan Pengetahuan Remaja Mengenai Kesehatan Reproduksi - Fransiska Quaesita Qory Lorenz; Henny Permatasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the form of implementation of health promotion through peer education in increasing adolescent reproductive health knowledge. The method used is the PRISMA 2009 algorithm with a literature search on the Proquest, Ebscohost, Scopus, and ScienceDirect databases. The results showed that of the seven articles analyzed, there were various peer education methods with an average significance value of p <0.05, indicating that these methods have the opportunity to increase reproductive health knowledge in adolescents. In conclusion, peer educators can be relied upon to increase adolescent knowledge about reproductive health. Keywords: Peer education, Reproductive health, Adolescents